2015
DOI: 10.5430/ijdi.v2n2p64
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis in the forefoot accompanied with joint pain is potentially associated with bone alterations

Abstract: We previously reported that the pathophysiology of hip Osteoarthritis (OA) may be due primarily to bone alterations. In the present case series, we describe the clinical results of 4 patients with forefoot OA and accompanying joint pain. Magnetic resonance imaging (MRI) and plain radiographs again revealed that bone alterations could have been the cause of the OA and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our study uncovered intraosseous MRI signal changes in various parts of the ankle in addition to the improvement of almost all cases of joint pain regardless of radiographic KL grading. We previously reported that forefoot OA showed similar OA and MRI bone alterations in accordance with joint pain, which disappeared as well 19 . Although bone alterations in and around the ankle joint occur due to weight bearing, most heal naturally.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our study uncovered intraosseous MRI signal changes in various parts of the ankle in addition to the improvement of almost all cases of joint pain regardless of radiographic KL grading. We previously reported that forefoot OA showed similar OA and MRI bone alterations in accordance with joint pain, which disappeared as well 19 . Although bone alterations in and around the ankle joint occur due to weight bearing, most heal naturally.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, bone alterations detected by MRI disappeared along with joint pain resolution 15 . We have also described that OA joint pain may be due to bone-related etiologies in various areas of the body 16 17 18 19 . Similarly to prior OA studies, we considered that a primary cause of ankle joint pain in this series might be bone alterations since MRI bone signal changes were observed in painful ankle regions that improved despite radiographic OA.…”
Section: Discussionmentioning
confidence: 98%